Realistic glottal motion and airflow rate during human breathing. Issue 9 (September 2015) - Scheinherr, Adam; Bailly, Lucie; Boiron, Olivier; Lagier, Aude; Legou, Thierry; Pichelin, Marine; Caillibotte, Georges; Giovanni, Antoine
Highlights The glottal motion during breathing was examined on 20 subjects using laryngofibroscopy and synchronized oral airflow measurements. Two groups were sorted out: a "static" group, gathering subjects with a constant glottal area during the breathing cycle; a "dynamic" group, gathering subjects with a time-varying glottal area. A correlation motion related to the airflow dynamics was found during inspiration. The realistic breathing mode (mobile glottis, non-sinusoidal flow rate) was shown to be an energy saving maneuver compared to an idealized mode (steady glottis, sinusoidal flow rate).